Influence of Treadmill Design on Gait: Does Treadmill Size Affect Muscle Activation Amplitude? A Musculoskeletal Calculation With Individualized Input Parameters of Gait Analysis - Woiczinski, Matthias; Lehner, Carolin; Esser, Thekla; Kistler, Manuel; Azqueta, Monica; Leukert, Johannes; Bauer, Leandra; Kraft, Eduard (Frontiers in Neurology, 2022)
With increasing age, gait changes often occur, leading to mobility problems and thus a higher risk of falling. Interest in training at home or at retirement homes has led to the development of “mobile treadmills.”. A difference in treadmill surface length may influence walking parameters (i.e., step length) and therefore may affect muscle activation. This led to the question: Does the treadmill size affect the muscle activation, i. e. with the length of the walking surface. The study aimed to investigate the influence of treadmill size, i.e., length of the walking surface, on gait pattern and to determine differences in the amplitude of muscle activation using a participant-specific musculoskeletal model (AnyBody Technology A/S, Aalborg, Denmark). For a prospective, randomized study gait parameters were collected from 47 healthy participants (aged 50.19 ± 20.58 years) while walking on two different treadmills, a small mobile treadmill (walking surface length 100 cm) and a conventional treadmill (walking surface length 150 cm), at their preferred speed, 2 km/h, and 4 km/h. Muscle activation amplitude patterns were similar between treadmills (M. gastrocnemius medialis: rmean = 0.94, M. gastrocnemius lateralis: rmean = 0.92, M. gluteus medius rmean = 0.90, M. gluteus minimus rmean = 0.94). However, the gait analysis showed a decreased preferred velocity (p < 0.001, z = 4.54), reduced stride length (preferred velocity: p = 0.03, z = -2.17; 2 km/h: p = 0.36, z = 2.10; 4 km/h: p = 0.006, z = 2.76), shorter stride time (2 km/h: p < 0.001, z = 4.65; 4 km/h: p < 0.001, z = 4.15), and higher cadence (2 km/h: p < 0.001, z = -4.20; 4 km/h: p = 0.029, z = -2.18) on the mobile treadmill than on the conventional treadmill. Our observations suggest that the treadmill design (e.g., a 50 cm difference in walking surface length) may not influence muscle activity amplitude during walking. However, the design of the treadmill may influence gait characteristics (e.g., stride length, cadence) of walking.